Improving the anti-inflammatory efficacy of dexamethasone in the treatment of rheumatoid arthritis with polymerized stealth liposomes as a delivery vehicle. Issue 9 (4th February 2020) - Wang, Qin; He, Liming; Fan, Donghao; Liang, Wenlang; Fang, Jiyu
Abstract : Polymerized stealth liposomes were developed for improving the anti-inflammatory efficacy of dexamethasone in the treatment of rheumatoid arthritis. Abstract : Rheumatoid arthritis (RA) is an autoimmune disease that causes chronic inflammation of the joints of the body. Although liposomes are a promising drug delivery vehicle, there is still a challenge of using conventional liposomes for the treatment of RA due to their short circulation time and physicochemical instability in blood vessels. Here, we report the formation of polymerized stealth liposomes composed of 1, 2-bis(10, 12-tricosadiynoyl)- sn-glycero -3-phosphocholine (DC8, 9 PC) and 1, 2-distearoyl- sn-glycero -3-phospho-ethanolamine-poly(ethyleneglycol) (DSPE-PEG2000 ) with a thin-film hydration method, in which DC8, 9 PC molecules are cross-linked in the bilayer of the liposomes by UV irradiation and the PEG chains present at the surface of the liposomes provide a stealth layer. We demonstrate that the polymerized stealth liposomes are stable and show long circulation time in blood vessels. They can be internalized by cells without significant toxicity. After being injected into arthritic rats, the polymerized stealth liposomes with loaded dexamethasone (Dex) show long blood circulation time and accumulate preferentially in inflamed joints, consequently suppressing the level of proinflammatory cytokines (TNF-α and IL-1β) in joint tissues, reducing the swelling of inflamed joints and alleviating the progression of RA. We believe that polymerized stealth liposomes can be used as a promising drug delivery vehicle for various therapeutic applications.